Estimating settlements of structures supported on cohesive soils / by Charles C. Ladd. - Ladd, Charles C. (Charles Cushing) (Tufts University. Tisch Library., 2019)
1 online resource (various pagings) : illustrations; "This paper was originally prepared for M.I.T. 1971 Special Summer Program 1.34S 'Soft Ground Construction' and has been revised for this presentation."; "April 9 & 10, 1973."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.